Oral Health Education Courses for University Students: Why Not? - Deok-Young Park, PhD; Deuk-Sang Ma, PhD; Alice M. Horowitz, PhD (Blackwell Publishing, 2004)
Oral health status can be maintained or enhanced through prevention-oriented practices of individuals and an environment conducive to oral health.